Interregional research and practical conference with international attendance "Epilepsy and Paroxysmal Conditions as an Interdisciplinary Problem"(19 February 2020) - D. A. Petrenko (IRBIS LLC, 2020)
The annual Interregional research and practical conference "Epilepsy and Paroxysmal Conditions as an Interdisciplinary Problem" was held in Moscow 19/02/2020, bringing together neurologists and epileptologists from Russia. The event was dedicated to the memory of Gagik N. Avakyan, who was President of Russian League Against Epilepsy (RLAE) for many years. The paper contains key messages of the plenary session.